How do you divide (2x^3+3x^2-8x+3)div(x+3)(2x3+3x2−8x+3)÷(x+3)?
2 Answers
Explanation:
So
Explanation:
"one way is to use the divisor as a factor in the numerator"one way is to use the divisor as a factor in the numerator
"consider the numerator"consider the numerator
color(red)(2x^2)(x+3)color(magenta)(-6x^2)+3x^2-8x+32x2(x+3)−6x2+3x2−8x+3
=color(red)(2x^2)(x+3)color(red)(-3x)(x+3)color(magenta)(+9x)-8x+3=2x2(x+3)−3x(x+3)+9x−8x+3
=color(red)(2x^2)(x+3)color(red)(-3x)(x+3)color(red)(+1)(x+3)color(magenta)(-3)+3=2x2(x+3)−3x(x+3)+1(x+3)−3+3
=color(red)(2x^2)(x+3)color(red)(-3x)(x+3)color(red)(+1)(x+3)+0=2x2(x+3)−3x(x+3)+1(x+3)+0
rArr(2x^3+3x^2-8x+3)/(x+3)⇒2x3+3x2−8x+3x+3
=(cancel((x+3))(2x^2-3x+1))/(cancel((x+3))
=2x^2-3x+1